Neural correlates of the sound facilitation effect in the modified Simon task in older adults - Manelis, Anna; Hu, Hang; Miceli, Rachel; Satz, Skye; Schwalbe, Marie (Frontiers in Aging Neuroscience, 2023)
Introduction The ability to resolve interference declines with age and is attributed to neurodegeneration and reduced cognitive function and mental alertness in older adults. Our previous study revealed that task-irrelevant but environmentally meaningful sounds improve performance on the modified Simon task in older adults. However, little is known about neural correlates of this sound facilitation effect. Methods Twenty right-handed older adults [mean age = 72 (SD = 4), 11 female] participated in the fMRI study. They performed the modified Simon task in which the arrows were presented either in the locations matching the arrow direction (congruent trials) or in the locations mismatching the arrow direction (incongruent trials). A total of 50% of all trials were accompanied by task-irrelevant but environmentally meaningful sounds. Results Participants were faster on the trials with concurrent sounds, independently of whether trials were congruent or incongruent. The sound effect was associated with activation in the distributed network of auditory, posterior parietal, frontal, and limbic brain regions. The magnitude of the behavioral facilitation effect due to sound was associated with the changes in activation of the bilateral auditory cortex, cuneal cortex, and occipital fusiform gyrus, precuneus, left superior parietal lobule (SPL) for No Sound vs. Sound trials. These changes were associated with the corresponding changes in reaction time (RT). Older adults with a recent history of falls showed greater activation in the left SPL than those without falls history. Conclusion Our findings are consistent with the dedifferentiation hypothesis of cognitive aging. The facilitatory effect of sound could be achieved through recruitment of excessive neural resources, which allows older adults to increase attention and mental alertness during task performance. Considering that the SPL is critical for integration of multisensory information, individuals with slower task responses and those with a history of falls may need to recruit this region more actively than individuals with faster responses and those without a fall history to overcome increased difficulty with interference resolution. Future studies should examine the relationship among activation in the SPL, the effect of sound, and falls history in the individuals who are at heightened risk of falls.